2020
DOI: 10.15694/mep.2020.000214.1
|View full text |Cite
|
Sign up to set email alerts
|

Fully online OSCEs: A large cohort case study

Abstract: Objective Structured Clinical Examinations (OSCEs) are extensively used for clinical assessment in the health professions. However, current social distancing requirements (including on-campus bans) at many universities have made the co-location of participants for large cohort OSCEs impossible. While there is a developing literature on remote OSCEs, particularly in response to the COVID-19 pandemic, this is dominated by approaches dealing with small participant numbers. This paper describes our recent large sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…With slight modifications and creativity, it is possible to assess online almost all skills usually included in a face-to-face OSCE [ 3 ]. Trials also showed that good planning and training could overcome common hurdles to successful OSCEs, such as a large number of students, the use of simulated patients, and the operation of multiple concurrent stations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…With slight modifications and creativity, it is possible to assess online almost all skills usually included in a face-to-face OSCE [ 3 ]. Trials also showed that good planning and training could overcome common hurdles to successful OSCEs, such as a large number of students, the use of simulated patients, and the operation of multiple concurrent stations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Orientation programmes for students and faculty should be conducted to make them familiarize with synchronous online OSCE. 15 Limitations: The limitation of this study was the limited number of students. A large cohort of the students should be used to generalized the results.…”
Section: Discussionmentioning
confidence: 97%
“…Orientation programmes for students and faculty should be conducted to make them familiarize with synchronous online OSCE. 15 …”
Section: Discussionmentioning
confidence: 99%
“…With the onset on COVID it became impossible to hold face-to-face OSCE examinations. In common with other institutions, we introduced an online OSCE 39,40 . This has limitations compared to a face-to-face OSCE as the students cannot be assessed in tasks that require physical contact with patients but does provide a good assessment of other clinical tasks.…”
Section: Discussionmentioning
confidence: 99%